An Analysis of Code Switching in Boy William’s Vlog on Youtube - puji - laksono; Aprilia Novita (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
Today there are many people can speak more than one language. It makes them can switch from one language to others in one speech event. This paper explainstypes of code switching, factors that influence the use of code switching and the function of code switching Boy William’s Vlog. The research belongs to qualitative research. The data are in form of utterances spoken by the Boy William and his guests. The data are collected by observation. It is done by watching and recording the video and writing the data. Then dataare analyzed by content analysis. The steps in analyzing data are: selecting data, interpreting and drawing conclusion. The results shows that there are three types of code switching found, that are Intra-Sentential, Inter-Sentential and Tag Switching. Meanwhile, there are four factors that affect code switching; Participant, Solidarity, Status and Topic. While the function of code switching, six functions were found; Talking about Particular topics, Interjection, Express Solidarity, Intention of Clarifying The Speech Content for Interlocutors, Repetition Used for Clarification and Express Group Identification. Keywords:Types of code switching, Factors of code switching, Functions of code switching, Vlog.